System of transportation and sorting by base mobile working platforms with direct current electric drive - Sylin, Maksym (National Technical University "Kharkiv Polytechnic Institute", 2024)
The integration of direct current (DC) electric drives in mobile working platforms for transportation and sorting operations represents a significant step towards optimizing logistics and manufacturing processes. This study aims to explore the capabilities and efficiencies introduced by employing DC electric drives in such systems. The focus is on evaluating the performance, reliability, and adaptability of these platforms in various operational scenarios.
Keywords: systems of transportation; electric drives; mobile working platforms; logistics optimization; sorting